Rapid Precipitation: An Alternative to Solvent Casting for Organic Solar Cells. Issue 6 (29th January 2015) - Dattani, Rajeev; Telling, Mark T. F.; Lopez, Carlos G.; Krishnadasan, Siva H.; Bannock, James H.; Terry, Anne E.; de Mello, John C.; Cabral, João T.; Nedoma, Alisyn J.
Abstract: Rapid precipitation, immersion of a liquid formulation into a nonsolvent, is compared with drop casting for fabricating organic solar cells. Blends comprising poly‐3‐hexylthiophene (P3HT), phenyl‐C61‐butyric acid methyl ester (PCBM), and chlorobenzene were processed into bulk samples by using two distinct routes: rapid precipitation and drop casting. The resulting structure, phases, and crystallinity were analyzed by using small‐angle neutron scattering, X‐ray diffraction, differential scanning calorimetry, and muon spin resonance. Rapid precipitation was found to induce a finely structured phase separation between PCBM and P3HT, with 65 wt % crystallinity in the P3HT phase. In contrast, solvent casting resulted in a mixed PCBM/P3HT phase with only 43 wt % P3HT crystallinity. The structural advantages conferred by rapid precipitation were shown to persist following intense thermal treatments. Abstract : A drop in the bucket: Rapid precipitation shows promise for the processing of organic solar cells and introduces new challenges. Compared with drop casting, rapid precipitation allows for faster processing, finer phase separation, and nearly doubled polymer crystallinity.